Brain-derived neurotrophic factor (BDNF) plasma concentration in patients diagnosed with premature ovarian insufficiency (POI). (4th May 2017) - Czyzyk, Adam; Filipowicz, Dorota; Podfigurna, Agnieszka; Ptas, Paula; Piestrzynska, Malgorzata; Smolarczyk, Roman; Genazzani, Andrea R.; Meczekalski, Blazej
Abstract: Premature ovarian insufficiency (POI) is defined as a cessation of function of ovaries in women younger than 40 years old. Brain-derived neurotrophic factor (BDNF) is a protein critically involved in neuronal growth and metabolism. BDNF also has been shown to be important regulator of oocyte maturation. Recent data show that BDNF can be potentially involved in POI pathology. The aim of the study was to assess the BDNF plasma concentrations in patients diagnosed with idiopathic POI. 23 women diagnosed with POI (age 31 ± 7 years) and 18 (age 31 ± 3) controls were included to the study, matched according to age and body mass index. The BDNF concentrations were measured using competitive enzyme-linked immunosorbent assay (ELISA). Hormonal and metabolic parameters were measured in all individuals, in controls in late follicular phase. The POI group demonstrated lower mean plasma concentrations of BDNF (429.25 ± 65.52 pg/ml) in comparison to healthy controls (479.75 ± 34.75 pg/ml, p = 0.0345). The BDNF plasma concentration correlated negatively ( R = −0.79, p < 0.001) with number of months since last menstrual period. There was a positive correlation between BDNF and progesterone in controls. In conclusion, POI patients show significantly lower BDNF plasma concentration and it correlates with the duration of amenorrhea. This observation brings important potential insights to the pathology of POI.